Three-dimensional domain swapping in p13suc1 occurs in the unfolded state and is controlled by conserved proline residues - Rousseau, F. (The National Academy of Sciences, 2001)
p13suc1 has two native states, a monomer and a domain-swapped dimer. We show that their folding pathways are connected by the denatured state, which introduces a kinetic barrier between monomer and dimer under native conditions. The barrier is lowered under conditions that speed up unfolding, thereby allowing, to our knowledge for the first time, a quantitative dissection of the energetics of domain swapping. The monomer–dimer equilibrium is controlled by two conserved prolines in the hinge loop that connects the exchanging domains. These two residues exploit backbone strain to specifically direct dimer formation while preventing higher-order oligomerization. Thus, the loop acts as a loaded molecular spring that releases tension in the monomer by adopting its alternative conformation in the dimer. There is an excellent correlation between domain swapping and aggregation, suggesting they share a common mechanism. These insights have allowed us to redesign the domain-swapping propensity of suc1 from a fully monomeric to a fully dimeric protein.